Curriculum Development Pattern of Merdeka PAI in Realizing 21st Century Competencies in Schools - Syifa Fatihatul Mubarokah; Fathul Barr Narwin Adimanggala; Pitra Gosha Patriasya (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2026)
The development of the Merdeka Curriculum in Islamic Religious Education (PAI) represents a strategic response to the demands of 21st-century competencies, which emphasize critical thinking, creativity, collaboration, and communication (4C). This study aims to analyze the development pattern of the Merdeka Curriculum for PAI and its implications for fostering 21st-century competencies at the school level. Employing a qualitative approach through a structured literature review of publications from accredited national journals (Sinta) and international databases (Scopus) published between 2015 and 2025, the data were analyzed thematically using Braun and Clarke’s framework to identify patterns, challenges, and best practices in curriculum development. The findings reveal that the dominant development pattern is collaborative-decentralistic, representing a form of directed autonomy in which the government establishes the framework of learning outcomes, while educational institutions engage in curriculum co-creation with teachers, students, and the community. This pattern promotes local relevance and creates opportunities for integrating Islamic values with project-based learning practices and authentic assessment. However, the success of this pattern depends strongly on teachers’ capacity, valid assessment mechanisms, the availability of digital resources, and policy support. The practical implications of this study highlight the need for a systematic development process, including needs analysis, co-design, prototyping, and validation, as well as the strengthening of teacher professionalism and the development of calibrated 4C assessment instruments. These efforts are essential to ensure that the Merdeka Curriculum for PAI can effectively shape students’ character and 21st-century competencies.